Neoliberalismo e neoconservadorismo nas políticas educacionais brasileiras: os discursos do movimento Escola Sem Partido - Costa, Regina Alice Rodrigues Araujo (2023)
This research aims to investigate the influences of neoliberal and neoconservative society on Brazilian educational policies and the discourses of the School Without a Party (Escola Sem Partido - ESP), in the context after the 2016 coup until the year 2022. The thesis presented is that the ESP is the effect of disputes and articulations of neoliberal and neoconservative discourses, which are based on depoliticization, authoritarianism, productivism, mercantile logic, competitiveness, with the effects of policies to marginalize socially vulnerable groups and destabilize the democratic system. To this end, in the epistemological constructions, we use the post-structuralist theoretical perspective, where we mobilize discourse theory as a theoretical contribution and discourse analysis tool. The research methodology is based on bibliographical and documentary research and, secondarily, we used virtual social network analysis to investigate the recording of virtual social dynamics using the SocialBlade tool. Our corpus of analysis is made up of: The main bills presented at national level that have a correlation with the ESP; Social network pages and websites of the ESP movement and program; Speeches made in interviews with ESP coordinators and supporters on virtual platforms; Statements made by administrative bodies on the ESP (Federal Public Prosecutor's Office, Federal Supreme Court, Ministry of Education); Notification document from the United Nations on the progress of bills that deal with the ESP; Speeches directed at education in the Government Plan of the candidates for the Presidency of the Republic in the 2018 elections; Miguel Nagib's official statement of withdrawal from Escola Sem Partido in 2020. As findings, we have that the ESP, which initially supported a discourse based on the empty signifier of being opposed to indoctrination in Brazilian education, from 2016 to 2022 was articulated to other demands, based on traditional and neoconservative values; education; educational policies and politics. As considerations, we reflect that the neoliberal and neoconservative developments have been gestating for some time within Brazilian society, in a process of hegemonic disputes and different discursive and articulatory mobilizations. These processes of disputes and influence are contingent, precarious and marked by political games of articulation that produce slippages due to historical, political and social contexts. The antipetista, moral conservative and neoliberal semantic field has produced a hegemonic order in which neoconservatism, neoliberalism and the ESP Movement have found a fruitful scenario for the capillarization of their discourses and ideals. However, there are possibilities for cracks in the hegemonic models, so that other political forces are also competing for democratic educational projects. The study has contributed to a new perspective in the analysis and understanding of the discursive, antagonistic and emerging relationships between neoliberalism, neoconservatism and the ESP.